THE ROLE OF AGRICULTURAL EXTENSIONIST ON THE PRODUCTIVITY OF COFFEE FARMING - Sulaksana, Jaka; Andayani, Sri Ayu; -, Astriyani (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2024)
Extension officers have a very important role, namely as a non-formal learning tool that provides knowledge on how to run a farm that can help improve the quality of farmers, skills, and profit income in farming. Therefore, research was conducted related to the role of agricultural extension agents on farming and the relationship between the role of agricultural extension agents on productivity. The purpose of this study is to determine the role of agricultural extension workers as facilitators, dynamists, consultants, organizers, analyzers in coffee farming. And the relationship between the role of agricultural extension agents on farming productivity using a descriptive quantitative method of measuring the Likert scale and rank correlation test to analyze the relationship between the role of agricultural extension agents and productivity. The sample size used was 32 with a sampling technique, namely the saturated sample contained in Non Probability Sampling. The results obtained by the role of agricultural extension agents in coffee farming agricultural extension agents as facilitators were 3.56 Medium categories, extension agents as dynamicators 3.29 Medium categories, extension agents as consultants 3.53 High categories, extension agents as organizers 3.61 High categories and extension agents as analyzer of 2.99 Medium category. Extension agents with a high category in coffee farming in weak sugih namely the role of extension agents as consultants and as organizers. for extension agents as facilitators, dynamists and analyzers, scores in the Moderate category are obtained. As for the rank correlation analysis test, it is used to analyze the relationship between the role of extension workers and productivity. The results show that there is a relationship with a correlation value of 0.383, with a low correlation criterion.